The Moderating Role of POSM (Point of Sales Material) in the Relationship Between Application Quality and Familiarity on Trust and Purchase Intention - Badawi Badawi (Universitas Muhammadiyah Yogyakarta, 2024)
Currently, e-commerce is one of the shopping centers in Indonesia. The growth of online transactions indicates a broader market presence, yet it simultaneously highlights a highly competitive and dynamic business landscape. This study aims to analyze the direct effect of application quality and familiarity on trust and purchase intention in e-commerce consumers. This study also analyzes the moderating role of Point of Sales Materials (POSM) in strengthening the direct effect of application quality and familiarity on trust and purchase intention. This research was a quantitative study involving e-commerce consumers in West Java. The sample in this study was taken using a stratified random sampling method, resulting in a sample size of 230 participants. Data collection was obtained by distributing questionnaires, with subsequent analysis performed using a structural equation model with Smart-PLS4. The results showed that application quality affects trust but does not affect purchase intention. Furthermore, familiarity affects trust and purchase intention. Trust was also shown to affect purchase intention. Further tests indicate that POSM effectively moderates the effect of application quality and familiarity on purchase intention but does not moderate their effect on trust. Therefore, this study contributes to the development of e-commerce and fills the literature gap in online marketing research. The study recommends enhancing application quality and user familiarity, customer trust, and purchase intention in e-commerce. Additionally, discounts and promotional concepts should be strengthened to amplify the influence of application quality and familiarity on consumer purchase intention in e-commerce.